Chairperson and CEO foreignness and CG quality of emerging markets MNCs: Moderating role of international board interlocks - Tunyi Tunyi Abongeh (International Journal of Finance and Economics, 2022)
We examine whether foreign chief executive officers (FCEOs) and foreign independent board chairpersons (FIBCs) improve on the corporate governance (CG) practices of emerging market multinational corporations (EMMNCs) through governance spill over. We use hand-collected data for 80 listed Nigerian multinational corporations for the period 2011–2016 (480 firm-years) and apply a three-stage least squares regression to address endogeneity issues. Our findings show international exposure of EMMNCs motivate appointment of FIBCs and FCEOs who positively affect their CG quality. In addition, international board interlocks positively moderate the likelihood of FCEOs to export and enhance EMMNCs' CG quality, but negatively moderate FIBCs impact on CG practices of EMMNCs. Finally, we develop a framework to show how EMMNCs' CG practices are exemplary to local firms in the home country who may mimic these governance practices. We contend the repeated game of governance spill-over and mimetic isomorphism drives the evolution of CG institutions and, potentially, will generate institutional change in CG practices in emerging markets.